Vacancy-coordinated hydrogen evolution reaction on MoO3−x anchored atomically dispersed MoRu pairs. Issue 24 (6th June 2019) - Liu, Suli; Chen, Cheng; Zhang, Yuefeng; Zheng, Qiuhui; Zhang, Sudi; Mu, Xueqin; Chen, Changyun; Ma, Jianmin; Mu, Shichun
Abstract : Enhanced electrocatalytic HER is demonstrated by constructing atomically dispersed MoRu pairs with abundant dangling unsaturated O and Ru vacancies on rGO-MoO3− x using an in situ versatile electrostatic assembly strategy. Abstract : Surface ion vacancy engineering at the atomic scale has attracted much attention to efficiently improve the electrocatalytic activity for the hydrogen evolution reaction (HER). Especially, compared with anion vacancies, cation vacancies are more challenging to generate, and studies on the structure–activity relationship of ion vacancy-rich metal oxide catalysts are still lacking. Herein, by means of abundant dangling unsaturated O and Ru vacancies, we report atomically dispersed MoRu pairs (rGO-MoO3− x –MoRu) stabilized with well-coupled graphene and MoO3− x . The atomically dispersed state of MoRu sites is confirmed by both high-angle annular dark-field scanning TEM (HAADF-STEM) and X-ray absorption fine structure (XAFS) measurements. As a result, rGO-MoO3− x –MoRu pairs show outstanding HER performance with very low overpotentials of 20 and 60 mV at 10 mA cm −2 under alkaline and acidic conditions, and maintain steady hydrogen bubble evolution continuously for 35 h. Meanwhile, for HER activity, they exhibit a positive correlation with the amount of oxygen vacancies, resulting in a favorable change in the adsorption behavior of H atoms on their neighboring Mo or Ru atoms.